High conductivity of novel ti0.9ir0.1o2 support for pt as a promising catalyst for low-temperature fuel cell applications - Tai Thien, Huynh; Huynh, Tai Thien; Vo, Dai-Viet N.; At Van, Nguyen; Vi Thuy, Thi Phan (2018)
The demand of robust and efficient catalyst for low temperature fuel cells has emerged in recent years to replace unstable commercial Pt/C catalyst. Here, Novel nanostructured Ti0.9Ir0.1O2 was synthesized and utilized as a catalyst support for Pt. The novel Ti0.9Ir0.1O2 support is synthesized by a